Comparison Between General and Spinal Anesthesia in the Effect on Hemodynamic Stability in Patients Undergoing Hernia Repair in Hospitals in Karbala, Iraq - Kadhim, Adnan Abdul Adheem; Salem Al-Khikani, Haider Ahmed Jalab; Hamza, Qasim Muhammad; Habib, Yass Khudair; Hussein, Muhammad Mohsen; Muhammad, Hassan Taqi (Knowledge Dynamics, 2025)
Background: Among the various methods, drugs, strategies, and guidelines for optimal anesthesia selection, the anesthesia and critical care staff primarily aim to choose the anesthetic with the least risk to the patient. Spinal anesthesia is one of the most effective and commonly used forms of anesthetic for hernia repair procedures. This study aims to provide an updated and accurate analysis of patients undergoing hernia repair at Karbala's Al-Hassan Hospital and Al-Hussein Medical City. Methods: We divided 100 patients who underwent herniotomy into two groups based on the type of anesthesia received: 50 patients received spinal anesthesia (SA), and 50 received general anesthesia (GA). The analysis included patient age, weight, changes in blood pressure, and pulse rate. To ensure comprehensive monitoring, patients aged 20 to 90 years were followed before, during, and after the procedure. Results: The results indicate greater hemodynamic stability in patients who received SA, with approximately 56% of patients demonstrating stable parameters compared to 40% in the GA group. However, higher blood pressure was observed more frequently in the GA group (32%) compared to the SA group (24%). Similarly, lower blood pressure was more common in GA (28%) than in SA (20%). Heart rate analysis revealed that SA resulted in greater stability, with 56% of patients maintaining a stable heart rate, compared to 32% in the GA group. Conversely, an increased heart rate was observed in 34% of patients in the SA group compared to 60% in the GA group. A decreased heart rate was reported in 10% of SA patients and 8% of GA patients, further supporting the conclusion that SA provides more stable outcomes. Conclusions: Spinal anesthesia was found to be superior to general anesthesia in maintaining heart rate and blood pressure stability at normal or minimally fluctuating levels.